Disinfection of ICU Room: Using the New Technologies for Diagnosis and Decontamination of Infections - Mostafa Mohammadi; Seyed Ali Dehghan Manshadi; Omid Rezahosseini (Archives of Anesthesia and Critical Care, 2016)
No Abstract